THE ROLE OF EMPLOYEE EMPOWERMENT IN IMPROVING EMPLOYEE PERFORMANCE AT SHANGHAI “JESSIVAR” KIAWA PEANUT FACTORY - Henry Longkutoy; S. L. H. V. Joyce Lapian; Ferdinand Tumewu (Universitas Sam Ratulangi, 2023)
The success of company management is primarily determined by utilizing human resources, where company managers must pay attention to employees' attitudes, behaviour, desires and needs to encourage employees to improve their performance. The final project aims to determine the observation of employee empowerment at Shanghai